The Investment Technology of Foreign and Domestic Institutional Investors in an Emerging Market - Patnaik, Ila (IMF Working Papers; Working Paper ;, 2013)
The literature on the investment technology of foreign versus domestic investors has inconclusive results. This paper revisits the question, with a focus on decomposing portfolio performance into asset allocation and security selection. We document signicant differences in exposure to systematic asset pricing factors between foreign and domestic investors. A quasi-experimental strategy is introduced, for comparing security selection after controlling for diferences in asset allocation. Our results show that foreign investors in India do remarkably poorly at security selection.